Definition and validation of serum biomarkers for optimal differentiation of hyperferritinaemic cytokine storm conditions in children: a retrospective cohort study. (August 2021) - Kessel, Christoph; Fall, Ndate; Grom, Alexei; de Jager, Wilco; Vastert, Sebastiaan; Strippoli, Raffaele; Bracaglia, Claudia; Sundberg, Erik; Horne, AnnaCarin; Ehl, Stephan; Ammann, Sandra; Wouters, Carine; et al.
Summary: Background: Cytokine storm syndromes are life-threatening complications that can occur in children with rheumatic conditions (macrophage activation syndrome [MAS]), inherited cytotoxicity defects (ie, primary haemophagocytic lymphohistiocytosis [HLH]), or as a result of infection or malignancies (ie, secondary HLH). To adequately steer treatment, an early and clear discrimination of these entities is essential. We aimed to define and validate serum biomarker profiles that can differentiate between primary HLH, secondary HLH (predominantly infection-associated), and MAS associated with systemic juvenile idiopathic arthritis (systemic JIA-MAS). Methods: In this multicentre, retrospective, cohort study, serum samples from patients (0–18 years) with a clinical diagnosis of primary HLH, secondary HLH, or systemic JIA-MAS were analysed by immunoassays for 55 cytokines and chemokines. Serum samples were collected from patients treated at seven clinical centres in Europe and North America. 15 serum biomarkers were validated using an independent commercial assay, and the diagnostic accuracy of the best performing biomarkers was tested in an independent validation cohort. Findings: Serum samples were collected between Dec 7, 2010, and Jan 26, 2018. In the discovery cohort of 43 patients (24 girls and 19 boys) multi-marker analyses revealed distinct serum biomarker profiles associated with primary or secondary HLH versus systemic JIA-MAS. Ten biomarkers were identified that were differentially elevated in either HLH or systemic JIA-MAS and distinguished between these clinical entities, six of which were tested in an independent validation cohort of 79 patients (34 girls and 45 boys). Serum concentrations of S100A12 and interleukin-18, as well as ratios of both S100A12 and IL-18 with chemokine (C-X-C motif) ligand (CXCL)9 and CXCL10 were identified as the most promising candidates for differential diagnostics. Interpretation: At initial presentation, when it is unclear whether a patient with excessive hyperferritinaemic inflammation has primary HLH, infection-associated secondary HLH, or MAS, high serum concentrations of S100A12 indicate an initial differential diagnosis of systemic JIA-MAS, thus helping to guide subsequent treatment decisions. We therefore suggest the inclusion of serum S100A12 and IL-18 in the diagnostic investigations for hyperferritinaemic syndromes; however, the definition and introduction of universially applicable cutoff values are still required. Funding: German Research Foundation, the Center for Interdisciplinary Clinical Research at University Hospital Muenster, the EU's Horizon 2020 research and innovation programme, and the Deutsche Kinderkrebsstiftung.